Valuing the willingness to pay for heritage institutions in Singapore - Lui, Yu Sen (Nanyang Technological University, 2023)
This study estimates the individual willingness to pay (WTP) and the total economic value (TEV) of six national museums of Singapore: the National Museum of Singapore, the Asian Civilization Museum, the Peranakan Museum, the Malay Heritage Center, the Indian Heritage Center, and the Sun Yat Sen Nanyang Memorial Hall. We collect our data by a survey with 338 samples. Our survey design employs the contingent valuation method (CVM), particularly Double Bounded Dichotomous Choice approach while we estimate the WTP with both parametric and nonparametric method. The TEV’s are estimated by the approach of Chay & Greenstone (2005). Additionally, we analyse the determinants of WTP of each museum, providing policy makers with insights to make differentiated policies targeting population with different sociodemographic background and different museum. We also contribute to the literature concerning protest zeros by examining potential causes of protest zeros with our data.